Lime Hemp Concrete with Unfired Binders vs. Conventional Building Materials: A Comparative Assessment of Energy Requirements and CO2 Emissions - Rotem Haik; Isaac A. Meir; Alva Peled (Energies, 2023)
This work assesses the energy requirements and CO2 emissions of a building made of Lime Hemp Concrete (LHC) with alternative unfired binders as lime replacement, compared to buildings made of standard LHC, and several conventional building materials. The assessment is based on ISO 14040, which deals with Life Cycle Assessment (LCA), and examines two aspects: energy, including pre-use phase Embodied Energy (EE), and use phase Operational Energy (OE); and CO2 emissions, including pre-use phase Embodied Carbon (EC), and use phase Operational Carbon (OC). The EE and EC calculations are based on published databases, while OE and OC were obtained with EnergyPlus simulations. The assessment refers to a specific case study in an arid region, with extreme diurnal and seasonal fluctuations of temperature and relative humidity. Using LHC with 100% unfired binder as lime replacement was shown to save up to 90% of the total energy consumption and CO2 emissions, as compared to conventional building materials. The findings of this research clearly demonstrate the high potential of LHC with unfired binders as lime replacement, which possesses the lowest energy requirements and CO2 emissions, illustrating the potential for a building with significantly low environmental impact over its life cycle, i.e., when calculating both EE and EC, and OE and OC.